Promotional training through outdoor advertisements and digital media publications - Fajar Junaedi; Filosa Gita Sukmono (Community Empowerment, 2021)
SD Muhammadiyah Kalangan is located in Baturetno Village, Banguntapan, Bantul, Yogyakarta Special Region. The location of SD Muhammadiyah Kalangan is actually strategic because it is on the border of Bantul Regency, Yogyakarta City and Sleman Regency, however the competition is very tight. Within a 5-kilometer radius, there are at least 7 schools, both public and private elementary schools. The location of SD Muhammadiyah Kalangan is far from the highway, so the name of the school is not known to the public. In online mass media, the name SD Muhammadiyah Kalangan also appears very rarely. In fact, the publication of school activities in online mass media is important. Based on these two issues, this service program will focus on increasing school promotion through outdoor advertising and publications in the mass media. Activities are carried out with advertising workshops and digital media publications. This activity produces school advertisements in the form of outdoor advertisements and publications in digital media as school promotion media.